Platelet-rich fibrin and silver nano-particles loaded chitosan treatment for post- laminectomy epidural scar adhesions: in vivo rats study model - Samah Fouad; Awad Rizk; Esam Mosbah; Mostafa M. Nabeeh; Walaa Awadin; Ayman S. Elmezayyen; Ekramy Elmorsy; Adel Zaghloul (BMC Neuroscience)
Abstract Objective Epidural scar fibrosis commonly leads to functional disability and pain following spinal surgery and is a prevalent manifestation of Failed Back Surgery Syndrome (FBSS). This study aimed to evaluate the use of silver nano-articles (AgNPs) loaded on chitosan (Chi/Ag-NPs) with platelets-rich fibrin (PRF) gel for the reduction of post-laminectomy epidural scar adhesions. Methods A total of 90 male Sprague Dawley rats (255 ± 55gm) were randomized in-to six groups, each group with 15 rats: control group, laminectomy group, PRF group, Chi/Ag-NPs group, combined treatment group (PRF + Chi/Ag-NPs), and a group to prepare PRF. Lumbar laminectomy procedures were performed between L3-L5 in all rats except the control group. After a 30-days follow-up, macroscopic examination, histological studies, and mRNA evaluation for TGFβ-1and IL-6, were conducted. Results Data revealed that epidural scar adhesion, scaring, arachnoid involvement, dural thickness, as well as inflammation and TGFβ-1and IL-6 coding genes expression were significantly reduced in PRF group, Chi/Ag-NPs group, and combined group compared to the laminectomy group. Combined treatment showed more significant better outcomes. Conclusion The use of PRF with Chi/Ag-NPs as nano biomaterials could be considered a combination therapy for the reduction of EF post-laminectomy in a rat model.